USE OF SUBCUTANEOUS LONG-ACTING SOMATOSTATIN ANALOGUE OCTREOTIDE LAR IN A CHILD WITH CONGENITAL HYPERINSULINISM - Cheng, Hooi Peng; Wong, Jeanne Sze Lyn; Selveindran, Nalini M; Teoh, Sze Teik; Amin, Noor Arliena Mat; Tee, Pian Pian; Gan, Cheng Guang; Anand, L Alexis; Hong, Janet Yeow Hua (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Congenital hyperinsulinism (CHI) is characterised by inappropriate insulin secretion and severe hypoglycaemia in infancy. Subcutaneous (SC) short-acting somatostatin analogue is used as second line therapy in diazoxide unresponsive patients, either as multiple daily injections or via a continuous infusion. Long-acting somatostatin analogues such as octreotide-LAR or lanreotide can be considered after a trial of successful use of short-acting octreotide. Due to the rarity of cases, experiences of its usage in infants and children are mostly limited to small case series. We describe a 7.5 year old child with CHI who was successfully converted from continuous subcutaneous octreotide infusion to intramuscular (IM) octreotide LAR 4-weekly. RESULTS Our patient first presented with hypoglycaemia at 2-hourof-life. He was diazoxide-unresponsive and needed continuous SC octreotide infusion via a pump to maintain normoglycaemia. Genetic testing revealed paternally derived heterozygous ABBC8 non-sense mutation, which suggests a focal form of hyperinsulinism. The family opted to continue medical treatment. In addition, the appropriate imaging (18-F DOPA PET/CT) was not available in the local setting. He had a normal growth rate and neurodevelopment. To improve his quality of life, transition from a continuous subcutaneous infusion of short-acting octreotide (7 mcg/kg/day) to IM octreotide LAR 10 mg every 4 weeks was made at the age of 6 years 11 months. Octreotide infusion was gradually weaned off over 3 weeks with no hypoglycaemia. Frequent home blood glucose pre-meals 4-6 times per day and overnight were in the range of 4-6 mmol/L. The injections were tolerated well with no adverse effects over 6 months. Potential side effects were monitored regularly, which included liver function, thyroid function, IGF-1 and ultrasound abdomen. CONCLUSION Long-acting somatostatin analogue should be considered in children with CHI who are diazoxide-unresponsive after a trial of short-acting octreotide. Long term follow-up and monitoring of side-effects are required.